Effects of Corporate Governance Structures on Enterprise Risk Management Practices in Malaysia - Mohd-Sanusi, Zuraidah; Motjaba-Nia, Shayan; Roosle, Nurul A.; Sari, Ria Nelly; Harjitok, Agus (International Journal of Economics and Financial Issues, 2017)
The risk management requirement, as part of best corporate governance practices has become compulsory for the Public Listed Companies (PLCs) in Malaysia. This study examines on the existing governance structures including establishment of Risk Management Committee (RMC), board independence, auditor quality and institutional ownerships would influence the extent of Enterprise Risk Management (ERM) practices. The study derived the aggregate ERM scores in measuring the relevant control and risk management practices of PLCs. For the purpose of the study, governance structure is proxied by RMC, board independence, auditor quality and institutional ownerships. Using a sample of large companies, data were regressed using regression analysis, based on three regression models. The study found that the establishment of risk management committee provided greater awareness of ERM within particular organization. However, the other governance variables have made less contribution to the risk management awareness and practices within a particular organization. Keywords: enterprise risk management, corporate governance, Bursa listing requirement, monitoring mechanism, risk management committee JEL Classifications: G3, G31